Effectiveness of 0.9% sodium chloride irrigation and oral propolis in diabetic foot ulcer infection: A case study - Syaharuddin Syaharuddin; Fardi Fardi (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Diabetic foot ulcer (DFU) is a major complication of diabetes mellitus characterized by infection, delayed healing, and increased risk of amputation. Effective management requires both local infection control and systemic metabolic stabilization. This study aimed to analyze the clinical effectiveness of combined 0.9% sodium chloride wound irrigation and oral propolis supplementation in reducing infection indicators in a patient with DFU. Research Methodology: A descriptive single-case study design was conducted in an inpatient ward of a secondary-care hospital in Makassar, Indonesia, over three consecutive days (March 9–11, 2025). One adult patient with post-debridement DFU and clinical signs of infection was selected using purposive sampling. Infection indicators (rubor, tumor, purulent exudate) and random blood glucose levels were assessed daily. Data were analyzed using within-case effect estimation, including percentage change, composite Infection Severity Index (ISI), and non-overlapping data analysis. Inferential statistics were not applied due to the single-case design. Results: Within three days, the purulent exudate resolved completely, and the composite ISI decreased by 66%. Random blood glucose declined from 300 mg/dL to 120 mg/dL (−60%), indicating a large within-case effect size. All measured infection indicators demonstrated consistent directional improvement. Conclusion: The combined intervention showed strong descriptive clinical effectiveness in reducing local infection severity and improving glycemic control. These findings support further controlled studies to validate integrative immunometabolic strategies in DFU management